Self-assembling Plants and Integration across Ecological Scales - Hunt, Roderick; Colasanti, R.L (Annals of botany, 2007)
BACKGROUND AND AIMS: Although individual plants exhibit much complex behaviour in response to environmental stimuli, they appear to do so without any identifiable centres of organization. We review a special class of model with the aim of testing whether plants can effectively be self-assembling, modular-driven organisms, in the sense that whole-plant organization and behaviour emerges solely from the interactions of much smaller structural elements. We also review evidence that still higher-level behaviour, at the population and community levels of organization, can emerge from this same source. METHODS: In previous work we devised a special cellular automaton (CA) model of plant growth. This comprises a section depicting a two-dimensional plant in its above- and below-ground environments. The whole plant is represented by branching structures made up from identical 'modules'. The activity of these modules is driven by morphological, physiological and reproductive rulesets derived from comparative plant ecology, a feature which lends itself to experimentation at several ecological scales. KEY RESULTS: From real experiments using virtual plants we show that the model can reproduce a very wide range of whole-plant-, population- and community-level behaviour. All of these properties emerge successfully from a ruleset acting only at the level of the CA module. CONCLUSIONS: The CA model can, with advantage, be driven by C-S-R plant strategy theory. As this theory can ascribe a functional classification to any temperate angiosperm on the basis of a few simple tests, any community of such plants can be redescribed in terms of its 'functional signature' and the net environment that it experiences. To a valuable first approximation, therefore, a C-S-R version of the CA model can simulate the most essential properties both of natural vegetation and of its environment. We have thus achieved a position from which we can test a plethora of high-level community processes, such as diversity, vulnerability, resistance, resilience, stability, and habitat-community heterogeneity - processes which, if investigated on the scales truly required for a full understanding, would fall beyond the practical scope of even the largest real-life investigation.